The Omnibus Law in Indonesia: Legal and Technological Dimensions of Policy Reform in a Civil Law Context - Nanik Prasetyoningsih; Muhammad Nur Rifqi Amirullah; Zulfan (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2026)
In the digital governance era, the Omnibus Law also reflects Indonesia’s attempt to modernize its regulatory system through integrated and technology-driven policymaking. The Omnibus Law signifies a crucial reform in Indonesia's legislative and policy framework, especially affecting infrastructure and policy growth. Inspired by common law traditions, the legislation seeks to streamline restrictions and expedite economic progress. This article analyzes the implementation of omnibus legislation in Indonesia in relation to legal reforms within common law and civil law frameworks, highlighting their effects on infrastructure initiatives and policy efficacy. This study employs a comparative and qualitative research methodology to examine legal reforms, their execution, and the difficulties encountered in applying the omnibus law model inside a civil law jurisdiction. The findings underscore the Omnibus Law's capacity to optimize governance, draw investment, and improve regulatory clarity, while simultaneously mitigating the risks of legal inconsistency and public opposition. The study contributes to the discourse on how legal modernization and regulatory simplification reshape governance and society in Indonesia’s civil law context. This study contributes to the emerging discourse on digital constitutionalism within civil-law jurisdictions, highlighting Indonesia’s effort to balance innovation with constitutional accountability.